A new species of Monstrilla Dana, 1849 (Copepoda: Monstrilloida: Monstrillidae) from Korea, including a key to species from the north-west Pacific - Lee, Jimin; Chang, Cheon Young (Zootaxa, 2016)
A new species of monstrilloid copepod belonging to the genus Monstrilla Dana, 1849 is recorded from South Korea. Specimens were obtained between May of 2012 and January of 2014 from inshore waters along the coasts of the East Sea, South Sea, and Jeju Island, using a light trap installed at quays and wharves overnight. Monstrilla ilhoii sp. nov. is characterized by a remarkable combination of a large body size (females about 3.8 mm long, males about 2.8 mm long), a polygonal ridge pattern (cuticular reticulation) over the entire body surface, and an antennule armature featuring a supernumerary spiniform seta (4d3) in females and a dagger-shaped distal spine (62) in both sexes. In other respects M. ilhoii sp. nov. most closely resembles M. lata Desai & Bal, 1963; both species have one and three setae on the endopodal and exopodal lobes, respectively, of female leg 5, a horseshoe-shaped male genital apparatus with marked undulations along the whole distal margin, and six setae on each caudal ramus in both sexes. This paper provides a description of the new species, taxonomic remarks on its morphological features, and differential diagnoses with respect to its allies. Scanning electron microscopy was used to document significant morphological microcharacters. The species of Monstrilla known from five sub-regions of the north-west Pacific are enumerated with the source references, and keys to the females and males of these species are provided.